ANALISIS TERHADAP PELAKSANAAN PEMBERATAN PIDANA BAGI TENAGA KEPENDIDIKAN YANG MELAKUKAN TINDAK PIDANA PENCABULAN TERHADAP ANAK DALAM PUTUSAN PENGADILAN NEGERI MANNA NOMOR 7/PID.SUS/2018/PN.MNA. - Lowrencha, Lowrencha (Fakultas Hukum Universitas Tarumanagara, 2021)
Children have an important role to live the ideals of a nation. Protection of children that needs to be an important view of a nation so that children can grow and develop. Protecting children from sexual violence is one of the most important roles for the state. Sexual violence that occurs against children in general the perpetrator is a person who is in the closest environment to the child such as the home environment, the child's play environment to the rise of sexual violence against children in the school environment. Cases of sexual violence are increasing and perpetrators are unpredictable, such as current cases of child sexual violence committed by teachers are increasing day by day. In this case it takes an important role from parents, families and communities to be responsible for maintaining children's human rights in accordance with the law. Inseparable from the role of the state to be responsible in terms of providing and providing facilities and accessibility space for children.